Narrative interaction - Quasthoff, Uta M. (Studies in narrative ;, 2005)
Telling stories in conversations is intricately interwoven with the interactive and local functions of story telling. Telling stories demands a certain kind of context and in itself establishes a particular interactive reality. Thus, narration is a specific kind of verbal interaction, governed by contextualizing devices, genre-specific cooperative regularities and corresponding verbal features. It plays an important role in institutional as well as in private modes of communication. The volume focuses on narration as a contextualized and contextualizing activity, which allocates specific struc.